Love and Politics. The Marriages of Mary Tudor (1496–1533) in English Ballads and Chronicles - Walczyk, Katarzyna (Vade Nobiscum, tom XX/2019: Studia z historii politycznej i wojskowej, 2019)
Although there is a relatively rich bibliography on the Tudor period, much less has been written about Mary Tudor, the youngest sister of Henry VIII. The purpose of this research is to present the history of marriages of Mary Tudor, and also to confront the romantic lenegend which grow around her second marriage. This paper analyzes letters, chronicles and ballads from 16th c entury, w hich d escribe M ary’s e ngagements a nd m arriages. The data were collected from British History Online and Internet Archive. Obtained information can tell researchers a lot about Mary and her relations with Henry VIII, Louis XII, Francis I or Charles Brandon. The analysis of the romantic legend of the English princess is mostly based on ballads which contain many references to the other historical sources.